F Formulasi Sediaan Sabun Cair Dari Ekstrak Kulit Pisang Kepok (Musa normalis L) Dengan Basis Minyak Inti Kelapa Sawit (Palm Carnel Oil) - Hermawan, Gt Yudha; Noval, Noval; Hidayah, Nur; Audina, Mia (LPPM Universitas Sari Mulia, 2024)
Background: skin care cosmetics are body cleansers commonly known as soap. Soap is available in dosage form and is available in solid and liquid dosage form. Liquid soap is a preparation that is widely marketed because it is easier to use, the advantage of liquid soap is that it is easy to carry, store, and is more hygienic and does not get dirty quickly.Objective: To determine the effect of varying concentrations of palm kernel oil (Palm Carnel Oil) on the optimal formulation of kepok banana peel extract (Musa normalis L.) liquid soap formulation based on the results of physicochemical evaluationMethods: The research method used is experimental which provides intervention/manipulation and treatment of cause and effect of measurements.Conclusion: Of the four formulas in making liquid soap preparations from kepok banana peel extract (Musa normalis L.) with a base of palm kernel oil (Palm Carnel Oil), the best results were obtained from formula 1.